THE IMPLICATIONS OF THE MAIN FAVOURABLE FACTORS IN THE APPEARANCE OF VARIOUS FORMS OF CANCER AT THE LEVEL OF ORAL CAVITY MUCOSA - Cristian Budacu; Doriana Agop Forna; Oana Elena Ciurcanu; Alexandru Nemțoi; Earar Kamel; Constantin Mihai (Romanian Society of Oral Rehabilitation, 2018)
Our study aims to establish correlative elements between the role of the main contributing factors in triggering various forms of oral mucosal cancer and to quantify their contribution according to a number of characteristic parameters.Materials and Methods: The statistical study was conducted over a period of 5 years at the Oro-Maxilofacial Surgery Clinic of St. Spiridon Iasi on internalized patients diagnosed with oral mucosal cancer.Results and Discussions : A well-defined category of contributing factors correlates to a high percentage of oral or oropharyngeal cancer. In this hierarchy of favoritisers of the mucosa of the oral cavity, an important place is occupied by the consumption of tobacco and alcohol, which makes it difficult to separate the degree of contribution of one or the other of the two components.Conclusions: The dentist must have a more intense activity in raising awareness of oral cavity cancer patients, increasing the educational level of population and sensitizing patients to the harmful and oncogenic action of alcohol and smoking.